Fecundity and Ovarian Characteristics of Puntius gonionotus (Bloch/Bleeker) (Cyprinidae: Cypriniformes) (Journal of Bio-Science, 2007)
The exotic barb Puntius gonionotus was introduced into Bangladesh in 1987. Its faster growth rate, nice taste and compatibility with our culturable species have made it very popular food fish in Bangladesh. With a view to providing some basic information towards development of sustainable seed production of the species, a study was undertaken to determine the fecundity and ovary characteristics of the fish. The mean fecundity of 55 gravid females (of 11 length group) of Puntius gonionotus was obtained as 14321 with a range of 2254.67 to 6964.73 from fishes having a mean total length and mean body weight of 200.13±20.58 mm and 196±34.379 g respectively. The relationship between the fecundity (F) and total length (TL), total body weight (TW), ovary length (OL) and ovary weight (OW) were established. Regression analysis was made and the co-efficient of correlation (r) was calculated for each of the following F-TL, F-TW, F-OL and F-OW and the values of r were obtained to be 0.84, 0.84, 0.95 and 0.96 respectively. In all the cases linear relationships obtained were highly significant. Key words: Fecundity, Puntius gonionotus, ovarian characteristics. J. bio-sci. 14: 99-102, 2006